2004
DOI: 10.1055/s-2004-820894
|View full text |Cite
|
Sign up to set email alerts
|

Severe Abnormalities of the Pons in Two Infants with Goldenhar Syndrome

Abstract: We describe 2 cases of Goldenhar syndrome with severe abnormalities of the pons. The first case is a 10-month-old Caucasian female infant. At birth the girl showed polydactyly, labiopalatoschisis, right ear agenesis, left eye coloboma and vertebral anomalies. She also had marked hypotonia, severely reduced movements and respiratory and feeding abnormalities. She required gastrostomy at 5 months and tracheostomy at 7 months. Brain MRI scans showed moderate cerebellar hypoplasia and severe abnormalities of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Furthermore BD is not seen within the spectrum of pontocerebellar hypoplasias [1,9] . Aside from typical BD, Sener and Pane et al have described abnormalities in the brainstem, but these children showed a cleft instead of a disconnection at the level of the ponto-medullary junction [5,8] . The clefts involved the ventral region of the ponto-medullary junction, whereas the dorsal region was spared.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore BD is not seen within the spectrum of pontocerebellar hypoplasias [1,9] . Aside from typical BD, Sener and Pane et al have described abnormalities in the brainstem, but these children showed a cleft instead of a disconnection at the level of the ponto-medullary junction [5,8] . The clefts involved the ventral region of the ponto-medullary junction, whereas the dorsal region was spared.…”
Section: Discussionmentioning
confidence: 99%
“…This is the only reported case in the literature formally documenting a patient with both disease processes. One other report describes 2 children with Goldenhar syndrome and abnormalities of the pons, possibly supporting an underlying connection of the 2 conditions (Pane et al, 2004). There have been reported deaths of patients with PTCD secondary to recurrent infections (Macferran et al, 2010).…”
Section: Discussion and Literature Reviewmentioning
confidence: 97%
“…[ 26 ] Brain stem involvement detected by magnetic resonance imaging in patients with Goldenhar Syndrome has been also reported; however, the stem lesions are very severe, resulting in a poor general prognosis. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%